2017
DOI: 10.1111/joim.12701
|View full text |Cite
|
Sign up to set email alerts
|

Estimated glomerular filtration rate and the risk–benefit profile of intensive blood pressure control amongst nondiabetic patients: a post hoc analysis of a randomized clinical trial

Abstract: Intensive BP control may provide little or no benefit and even be harmful for patients with moderate-to-advanced chronic kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 47 publications
3
42
0
Order By: Relevance
“…However, statistical power depends more on the number of events than the number of patients, and the number of events for the primary outcome was 77 (14%), 249 (44%), 127 (23%) and 108 (19%) amongst patients with eGFR >90, 60-90, 45-60 and <45 mL min À1 /1.73 m 2 , respectively. Therefore, our estimation of the effect modification by eGFR was driven by a wide range of eGFR levels, which was also supported by Figure 3 in our original article showing a good potential of linearity in the hazard ratios including the one in the category of eGFR <45 mL min À1 /1.73 m 2 [2].…”
supporting
confidence: 80%
See 2 more Smart Citations
“…However, statistical power depends more on the number of events than the number of patients, and the number of events for the primary outcome was 77 (14%), 249 (44%), 127 (23%) and 108 (19%) amongst patients with eGFR >90, 60-90, 45-60 and <45 mL min À1 /1.73 m 2 , respectively. Therefore, our estimation of the effect modification by eGFR was driven by a wide range of eGFR levels, which was also supported by Figure 3 in our original article showing a good potential of linearity in the hazard ratios including the one in the category of eGFR <45 mL min À1 /1.73 m 2 [2].…”
supporting
confidence: 80%
“…Patients with eGFR <45 mL min À1 /1.73 m 2 also had higher levels of urinary albumin excretion and received more antihypertensive agents. Furthermore, we demonstrated that in the intensive blood-pressure (BP) control group, patients with lower eGFR achieved higher systolic BP and lower diastolic BP levels, resulting in higher pulse pressure [2]. These observations suggest a heterogeneity in the SPRINT CKD population in terms of both patient characteristics and response to intensive BP control measures, and question the validity of the approach to categorize them into a single group.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…This brings us to the post hoc analysis of SPRINT data by Obi et al . in the present issue in which 9361 non diabetic hypertensive adults with eGFR >20 mL per min per 1.73 m 2 were enroled and followed up for 3.26 years. The authors showed that cardiovascular benefit from intensive treatment became attenuated with lower eGFR.…”
mentioning
confidence: 98%
“…Moreover, there was an increased risk of acute kidney injury. Thus, intensive BP control as achieved in SPRINT may provide little or no benefit and even be harmful for patients with moderate‐to‐advanced chronic kidney disease .…”
mentioning
confidence: 99%